Early‐onset, fatal interstitial lung disease in STAT3 gain‐of‐function patients. Issue 12 (28th September 2021) - Gothe, Florian; Gehrig, Jonathan; Rapp, Christina K.; Knoflach, Katrin; Reu‐Hofer, Simone; Länger, Florian; Schramm, Dirk; Ley‐Zaporozhan, Julia; Ehl, Stephan; Schwerk, Nicolaus; Faletti, Laura; Griese, Matthias
Abstract: Gain‐of‐function variants in STAT3 are known to cause severe, multifaceted autoimmunity. Here we report three individuals with de‐novo STAT3 GOF alleles and early‐onset, severe interstitial lung disease manifesting during the first 3 years of life. Imaging and histology revealed different forms of interstitial pneumonia alongside fibrotic and cystic tissue destruction. Definitive diagnosis was established by postmortem whole exome sequencing and functional validation of two new STAT3 variants. Such lung‐predominant forms of STAT3 GOF disease expand the phenotypic spectrum of diseases associated with activating STAT3 variants and add to our understanding of this life‐threatening inborn error of immunity.